2005
DOI: 10.1093/ndt/gfk008
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Cbfa1 and Pit-1 in calcified artery of uraemic rats with severe hyperphosphataemia and secondary hyperparathyroidism

Abstract: These results suggest that medial layer vascular calcification in uraemic rats with severe hyperphosphataemia and SHPT may be caused in part by Cbfa1 and Pit-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 17 publications
3
58
0
2
Order By: Relevance
“…This transition has been reported to be mediated by Pit-1, a type sodium-dependent phosphate cotransporter 12) . In calcified aorta or uremic rats, mRNA levels of Pit-1 and Cbfa-1 have been shown to increase, supporting the evidence that Pit-1 modulates osteoblastic differentiation of VSMCs 15) . Seyama et al 16) demonstrated that elastin is a critical protein that regulates the phenotypic modulation of VSMCs and its expression is reduced during Pi-induced calcification 17) .…”
supporting
confidence: 55%
“…This transition has been reported to be mediated by Pit-1, a type sodium-dependent phosphate cotransporter 12) . In calcified aorta or uremic rats, mRNA levels of Pit-1 and Cbfa-1 have been shown to increase, supporting the evidence that Pit-1 modulates osteoblastic differentiation of VSMCs 15) . Seyama et al 16) demonstrated that elastin is a critical protein that regulates the phenotypic modulation of VSMCs and its expression is reduced during Pi-induced calcification 17) .…”
supporting
confidence: 55%
“…Support for these related mechanisms comes from the differential sensitivity of WT CaR to MG132 in the presence of the modulators: NPS R-568 renders CaR insensitive to MG132, whereas the amount of CaR is increased by MG132 treatment in the presence of NPS 2143. Overall, these results strongly suggest that CaR conformation defines CaR stability by serving as a checkpoint during receptor biogenesis, and provide a potential mechanism for CaR protein up-regulation in parathyroid glands of rats treated chronically with NPS R-568 (26,35).…”
Section: Discussionmentioning
confidence: 70%
“…70 -73 Extracellular Pi stimulates calcification in VSMC through inorganic Pi influx by NaPi-3 [73][74][75] and cell- surface Pit2 reorganization. 73,76 High ambient Pi accelerates mineralization 44,49 and stimulates surrogate markers of osteogenesis in VSMC, 49,77 spawning the hypothesis that high Pi stimulates "ossification" of VMSC. 77 Soluble Klotho not only suppresses baseline NaPi-3 activity but also abrogates high Piinduced upregulation of NaPi-3 mRNA and activity and suppresses calcification and maintains differentiation of VMSC.…”
Section: Pathogenic Role Of Klotho In Progression Of Ckd and Its Compmentioning
confidence: 99%
“…73,76 High ambient Pi accelerates mineralization 44,49 and stimulates surrogate markers of osteogenesis in VSMC, 49,77 spawning the hypothesis that high Pi stimulates "ossification" of VMSC. 77 Soluble Klotho not only suppresses baseline NaPi-3 activity but also abrogates high Piinduced upregulation of NaPi-3 mRNA and activity and suppresses calcification and maintains differentiation of VMSC. Pit1 might also act through mechanisms independent of Pi influx, 78 and suppression of Pit1 may affect cell proliferation.…”
Section: Pathogenic Role Of Klotho In Progression Of Ckd and Its Compmentioning
confidence: 99%